Determining the aerobic capacity (VO2max) of adult female population of Turkey - Boz Kaya, Büşra Didem (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Aerobic capacity (AC) data of workforce are needed for ergonomic design of the physically demanding jobs in industry to establish safe and productive work designs. Workforce performance and production output depend on sustaining the effort over a period of time that depends on AC and type of tasks. In addition, excessive cardiovascular load may put the individuals in the risks of cardiovascular diseases such as coronary heart disease. AC data are also needed to form baselines for treatment of patients and also for sports to determine the fitness levels. There are a number of studies performed around the world related to the AC of the various populations. These studies shows that AC varies among some world populations and within the sub groups of a given population due to the differences in genetics, lifestyle, nutrition, geographical region, fitness level, gender and age. Therefore, it is a need to develop AC norms for the population of Turkey. Therefore, the objectives of the study are (i) estimating the aerobic capacity of healthy (normal) adult female population of Turkey, (ii) examining the effects of age, BMI and job-group on AC and (iii) comparing the AC data of the female population of Turkey with the AC data of female population of other countries. A sample of 256 healthy adult female volunteers aged between 18 and 54 with family roots from all seven regions of Turkey participated in the study. A modified submaximal cycle ergometer test, called Astrand - Myhre Bike Test, was used to collect AC data from the participants. Based on the statistical analysis results, mean and std of AC was found as 2 ± 0.2 l/min and 32.3 ± 7.8 ml/kg/min. The mean values of VO2max are decreasing from 18-24 years group to 45-54 years group and from under-weight group to obese group. In contrary, regular exercise had significant positive effect on AC. The established norms can serve as baseline in industrial work design and also clinical and sports settings. The results were compared with other world populations.
Keywords: Aerobic exercises.